5x+2-(x-1)=

Simple and best practice solution for 5x+2-(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2-(x-1)= equation:


Simplifying
5x + 2 + -1(x + -1) = 0

Reorder the terms:
5x + 2 + -1(-1 + x) = 0
5x + 2 + (-1 * -1 + x * -1) = 0
5x + 2 + (1 + -1x) = 0

Reorder the terms:
2 + 1 + 5x + -1x = 0

Combine like terms: 2 + 1 = 3
3 + 5x + -1x = 0

Combine like terms: 5x + -1x = 4x
3 + 4x = 0

Solving
3 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 4x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 4x = 0 + -3
4x = 0 + -3

Combine like terms: 0 + -3 = -3
4x = -3

Divide each side by '4'.
x = -0.75

Simplifying
x = -0.75

See similar equations:

| t=c+Crt | | -2x+7x=6(x-2)-(x-12) | | -4.2952x=34.79112 | | 6.2x-1.7=1.6x+16.7 | | x-22=-(9-8x) | | 2Ix+6I-4=12 | | 100-50+9-8= | | d=c+Crt | | V=5.4 | | 4.2952x=34.79112 | | 2X-4(5-X)=8-5X | | 4p^2+3pq-1q^2=0 | | -(4+8v)=-2(v-8)-6v | | 6x+5=x+6 | | -[7z-(13z+2)]=2+(5z+7) | | 3x-12forx=5 | | 6x^3+4=52 | | x/4-y/3=2 | | 5+4q=10+3q | | 28000/8=n | | 70/8=X/12 | | 3z-9=0 | | 3(x-2)-x=2(2x+11) | | 6(z+4)=5(z-2)+z | | z^2-40z+c=0 | | 2x-13=8x+1 | | 7x+5=9z-3 | | 0.35x+0.20(230-x)=54.25 | | 5(2x-3)+18=-8(x-2)+12x-1 | | 295+35d=350+33d | | 9m=-40+85 | | S=.5n(a+l) |

Equations solver categories